Flood Risk Analysis in Gajah Wong River, Yogyakarta City - Slamet Suprayogi; Suci Purnama Sari; Husnul Khotimah Setiacahyandari (School of Postgraduate Studies, Diponegoro Univer, 2024)
Evaluation of flood events in an area is essential to minimize its impacts by conducting hydrological and hydraulic river modeling. In 2016 and 2022, the events led to the breach of the Gajah Wong River levee, causing the floodwater to overflow and inundate residential areas, reaching a height of 2 meters. This study aims to analyze the risks posed by the Gajah Wong River overflow, while also identifying the elements at risk due to the potential of flooding. The flood inundation scenario modeling using Hec-RAS requires input such as peak discharge, Digital Terrain Model (DTM), and Manning's coefficient. High-resolution aerial photo extraction is employed to generate DTM and identify buildings affected by flood inundation, in accordance with the flood modeling. The rational method is used to calculate the peak discharge, utilizing the maximum daily rainfall data from 2001 to 2021. The results show that there was a significant expansion of inundation that reached 4.826 m2 for the 2-year and 50-years flood return periods. However, in terms of the flood impact on buildings, an area of 30.350,68 m2 is affected for the 2-year return period, and it expands to 35.439,05 m2 for the 50-year flood.